Promising Drug Candidates and New Strategies for Fighting against the Emerging Superbug Candida auris - Muriel Billamboz; Zeeshan Fatima; Saif Hameed; Samir Jawhara (Microorganisms, 2021)
Invasive fungal infections represent an expanding threat to public health. During the past decade, a paradigm shift of candidiasis from Candida albicans to non-albicans Candida species has fundamentally increased with the advent of Candida auris. C. auris was identified in 2009 and is now recognized as an emerging species of concern and underscores the urgent need for novel drug development strategies. In this review, we discuss the genomic epidemiology and the main virulence factors of C. auris. We also focus on the different new strategies and results obtained during the past decade in the field of antifungal design against this emerging C. auris pathogen yeast, based on a medicinal chemist point of view. Critical analyses of chemical features and physicochemical descriptors will be carried out along with the description of reported strategies.